Incidence and risk of cardiotoxicity associated with bortezomib in the treatment of cancer: a systematic review and meta-analysis. - Yi Xiao; Jin Yin; Jia Wei; Zhen Shang (PLoS ONE, 2014)
Background We conducted a systematic review and meta-analysis to clarify the incidence and risk of cardiotoxicity associated with bortezomib in cancer patients. Methods Databases from PubMed, Web of Science and abstracts presented at ASCO meeting up to July 31, 2013 were searched to identify relevant studies. Eligible studies included prospective phase II and III trials evaluating bortezomib in cancer patients with adequate data on cardiotoxicity. Statistical analyses were conducted to calculate the summary incidence, odds ratio (OR) and 95% confidence intervals (CIs) by using either random effects or fixed effect models according to the heterogeneity of included studies. Results A total of 5718 patients with a variety of malignancies from 25 clinical trials were included in our analysis. The incidence of all-grade and high-grade cardiotoxicity associated with bortezomib was 3.8% (95%CI: 2.6-5.6%) and 2.3% (1.6-3.5%), with a mortality of 3.0% (1.4-6.5%). Patients treated with bortezomib did not significantly increase the risk of all-grade (OR 1.15, 95%CI: 0.82-1.62, p=0.41) and high-grade (OR 1.13, 95%CI: 0.58-2.24, p=0.72) cardiotoxicity compared with patients treated with control medication. Sub-group analysis showed that the incidence of cardiotoxicity varied with tumor types, treatment regimens and phases of trials. No evidence of publication bias was observed. Conclusions The use of bortezomib does not significantly increase the risk of cardiotoxicity compared to control patients. Further studies are recommended to investigate this association and risk differences among different tumor types, treatment regimens and phases of trials.